Dodiri književne i filmske teorije: kratak uvod - Gilić, Nikica (Array, 2007)
Contacts between different disciplines in the humanities are frequent and extremely significant. This study concentrates mostly on the contacts made between literary and film theory in the work of authors concentrating on the questions of classification. After shortly discussing the usage of film examples in literary theory (N. Frye, K. Hamburger), the study tries to explain the usage of ideas from literary theory, philosophy and other traditional disciplines in the work of film theorists, postulating that the need for legitimization of a new discipline (dealing with a less respectable art form) often guided such argumentative strategy. After discussing contacts in various schools of thought, the study explains how the Croatian film theorists (A. Peterlic, H. Turkovic) have often used such sources as well, but always with the intention to illuminate their separate area of study, "borrowing" only those ideas that seem useful and adaptable to the context of the theory of cinema. Of course, this does not mean that their explanations and theories are always compatible: it is the rigour of analytical procedures that they share.